1990
DOI: 10.1172/jci114593
|View full text |Cite
|
Sign up to set email alerts
|

CAP37, a human neutrophil-derived chemotactic factor with monocyte specific activity.

Abstract: CAP37, an antimicrobial protein of human neutrophil granules, is a specific chemoattractant for monocytes. Purified to homogeneity by sequential chromatography over carboxymethyl Sephadex, G-75 Sephadex, and hydrophobic interaction HPLC, demonstratively endotoxin-free CAP37 was maximally chemotactic over a range of 1.3 X 10-9-10-8 M. Thus it was active in the same molar concentrations as formyl-methionyl-leucyl-phenylalanine. CAP37 lacked chemotactic activity for neutrophils and lymphocytes. In checkerboard as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
131
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(136 citation statements)
references
References 32 publications
4
131
0
Order By: Relevance
“…Experiments with the aim of characterising the haptotaxis and the receptor on the cells are in progress. Recently (Pereira et al, 1990) reported an N-terminal sequence identical to our hHBP and also described the His Ser mutation. They purified the protein, which they have named CAP37 and shown to be antimicrobial, from azurophile granules and showed that the protein was chemotactic for monocytes over the range 1.3 -10 nM.…”
Section: --S G V P P E V F T R V S S F L P W I R T T M R S F K L L Hnsupporting
confidence: 58%
“…Experiments with the aim of characterising the haptotaxis and the receptor on the cells are in progress. Recently (Pereira et al, 1990) reported an N-terminal sequence identical to our hHBP and also described the His Ser mutation. They purified the protein, which they have named CAP37 and shown to be antimicrobial, from azurophile granules and showed that the protein was chemotactic for monocytes over the range 1.3 -10 nM.…”
Section: --S G V P P E V F T R V S S F L P W I R T T M R S F K L L Hnsupporting
confidence: 58%
“…Azurocidin is released almost completely after granule mobilization. In contrast to, e.g., HNPs, which are released mainly into the phagolysosome [21], 90% of the azurocidin are released upon degranulation [17,19]. These three distinct properties of azurocidin favor the promiscuous mode of action that this protein displays.…”
Section: Azurocidin Is Unique Among the Pmn Granule Proteinsmentioning
confidence: 99%
“…26 Briefly, paraffin sections were deparaffinized in xylene, and rehydrated, and quenched for endogenous peroxidase. Cryostat sections were placed on gelatinized slides, and fixed in cold acetone.…”
Section: Immunohistochemical Studymentioning
confidence: 99%